Ultrastructure of coeloconic sensilla on postpedicel and maxillary palp of Megaselia scalaris (Diptera: Phoridae) - Kom Sukontason (2018)
The external morphology of coeloconic sensilla (peg-like sense organs protruding from deep pits) on the postpedicel (third antennal segment) and maxillary palp from a female Megaselia scalaris (Loew) is described using scanning electron microscopy. The pegs of the sensilla located on the postpedicel are "starfruit-like" in shape and are completely contained within deep depressions. Transmission electron microscopy showed that each peg has a thick and nonporous wall. The coeloconic sensilla of the maxillary palps are long, linear, and blunt-tipped and protrude over the cuticular surface. Possible functions of the sensilla are discussed. © 2005 Entomological Society of America.